ANALISIS COMOVEMENT PENDAPATAN SAHAM DENGAN PENDAPATAN OBLIGASI KORPORAT - MUHAMMAD AGUNG SUBEKTI ARI HARTADI, 090310624-L (2007)
This research examines (1) the influence of interest rate, lagged stock return (time t-1), current stock return (time t), and lead stock return (time t+l) towards bond return, and (2) understanding the influence power of interest rate, lagged stock return (time t-1), current stock return (time t), and lead stock return (time t+ 1) towards bond return, based bond rating categories. Observation data take by pooling that bundle of time series and cross section data in period January 2004 to December 2005. Determination of sample use method of purposive sampling. Multiple regresion technique was used to test the hyphotesis. In model of full sample interest rate and stock return in time t, proof in partially signification influence to bond return, where interest rate had a dominant influence in negative direction, where as stock return in time t had positive influence. In model of high grade sample and upper-medium grade sample, only interest rate that influence bond return. In model of lower-medium grade sample, interest rate, stock return (time t-l) and stock return in time (t), proof in partially significant influence to bond return. Where are interest rate had a dominant influence in negative direction. Stock return (time t-1) negative influences. whereas stock return in time (t) had positive influences.